Metode Everyone is Teacher Here Pada Materi Ikatan Kimia di Kelas X SMAN 1 Marawola - Milawati, Milawati; Pursitasari, Indarini Dwi; Tangkas, I Made (Jurnal Akademika Kimia, 2014)
Teaching and learning is a process involving interaction with active communication between students and teacher in educational activities. Therefore we need a method of learning that is focused to the students. This research uses learning Everyone is Teacher here method (ETH). The aim of this research was to determine the influence of the use of ETH methods on chemical content on learning outcomes and communication skills at tenth grade student of SMAN 1 Marawola generation 2013/2014, the sample of research was class XF as a class experiment with the application of learning ETH method (n = 20) and class XB as a control class without the use of learning ETH method (n = 21). Data were collected by observation, initial test, and final test. The data were analyzed by descriptively and right side t-test. The results of the analyzed of the data shows the average score in the experimental class = 83.95 and for control class = 70.36, both classes distributed were normally and have the variance (F test) are homogeneous. Testing hypotheses t test obtained tcount = 5.57 > ttabel = 1.68 with a significance level (Î±) = 0.05. In this case H1 was accepted and H0 was rejected, because of tcount were in H0 rejection region. The results suggest the application of learning ETH method has posirive side on learning outcomes and student communication skills in chemical material.